Entropic clocks in the service of electrical signaling: 'Ball and chain' mechanisms for ion channel inactivation and clustering. Issue 19 (22nd June 2015) - Zandany, Nitzan; Lewin, Limor; Nirenberg, Valerie; Orr, Irit; Yifrach, Ofer
Abstract : Electrical signaling in the nervous system relies on action potential generation, propagation and transmission. Such processes are dynamic in nature and rely on precisely timed events associated with voltage‐dependent ion channel conformational transitions between their primary open, closed and inactivated states and clustering at unique membrane sites. In voltage‐dependent potassium (Kv) channels, fast inactivation and clustering processes rely on entropic clock chains as described by 'ball and chain' mechanisms, suggesting important roles for such chains in electrical signaling. Here, we consider evidence supporting the proposed 'ball and chain' mechanisms for Kv channel fast inactivation and clustering associated with intrinsically disordered N ‐ and C ‐terminal regions of the protein, respectively. Based on this comparison, we delineate the requirements that argue for such a process and establish the thermodynamic signature of a 'ball and chain' mechanism. Finally, we demonstrate how 'chain'‐level alternative splicing of the Kv channel gene modulates the entropic clock‐based 'ball and chain' inactivation and clustering channel functions underlying changes in electrical signaling. As such, the Kv channel model system exemplifies how linkage between alternative splicing and intrinsic disorder enables functional diversity.